Functionalization of Carbon Nanotubes as Support Material of Pt/CNTs Catalyst for Proton-Exchange Membrane fuel Cell - Purniawan, Agung; Noerochim, Lukman; Sutarsis , Sutarsis; Oktaviano, Haryo Satriya; Sukmana, Hafidz Alim; Wicaksono, Muhamad Akbar; Rachman, Berlian Aulia; Jatimurti, Wikan; Susanti, Diah; Nurdiansyah, Hanifudin; et al. (IPTEK The Journal for Technology and Science, 2025)
The Proton Exchange Membrane Fuel Cell (PEMFC) is a type of fuel cell that converts hydrogen fuel into electrical energy. In PEMFC, platinum (Pt) supported by carbon black (CB) is frequently used as a catalyst. The catalyst has several constraints cause it to agglomerate and corrode during fuel cell operations. Carbon Nanotubes (CNTs) are a contender as a catalyst-supporting material because they offer superior properties such as hydrophobicity, conductivity, and surface area. This study used pH modifications in the synthesis process, morphology, and electrochemical performance of the Pt/CNTs catalyst to evaluate the reduced size of Pt particles and increased CNTs surface area. During the catalyst synthesis procedure, colloidal solutions with pH variations of 11 and 13 were utilized. TEM analysis showed that at pH 13, the produced Pt nanoparticles had the least average particle size of 4.2 nm, followed by 5.1 and 7.9 for pH 9 and 11, respectively. The best electrochemical performance was achieved in pH 13 samples with the largest active surface area of 40.33 m2/g, an onset potential of 0.798 V involving 4.01 electrons for the oxygen reduction reaction, and the lowest risk of deterioration.